Estudo do regime de precipitação na bacia hidrográfica do rio Capim - PA - NASCIMENTO, Marcos José Costa (2019)
This work has for objective to show the behavior of the regime of precipitation pluviométrica of Capim River Hidrografic Basin done through data of precipitation of five stations pluviométricas strategically distributed along Capim River with series of data with duration between 10 and 35 years. A frequency analysis was accomplished and of intensities of precipitation that considered monthly periods for identification of the monthly medium precipitation, annual medium precipitation and seasonal variation in São Domingos' stations, Badajós, Fazenda Maringá, Rondon of Pará and Tauiri. The stations are evenly distributed along Capim River and it was verified that of the headboard to the bass course of the river, the rainy period understands the months of January to April. The seasonal variation of the rains in the display that is in the summer, corresponding to the months of January, February and March, that it happens most of the total amount of annual precipitation, being understood among 40% in São Domingos and 54% in Rondon of Pará. It is noticed, clearly, that between the headboard and the low course of the river, there is an uniformity of the rainy period during the whole year. Already in relation to the less rainy period, it is noticed that there is a delay of two months between the headboard and the low course. Relating the rainy period and the drought period with the phenomena La Niña and El Niño, respectively, we concluded that the studied area is quite sensitive the those atmospheric phenomena.